Stress fractures in runners - Harrast, M. A.; Colonno, D. (Clinics in Sports Medicine, 2010)
Running has many beneficial effects, including cardiovascular and skeletal health. Poor training technique and a variety of risk factors may predispose runners to lower-limb overuse injuries affecting muscle, tendon, and bone. Injuries to the bone include stress reactions to full-fledged stress fractures. This article is designed to provide an understanding of the general concepts involving bone strain, risk factor assessment, and evaluation and treatment strategies for the runner with a stress fracture. The second half of the article presents more detail regarding each specific fracture seen in runners. The ultimate goal of this article is to provide the basics regarding stress fractures in runners from pathophysiology and general guidelines of evaluation and treatment and provide a quick reference regarding the details of each specific fracture encountered in clinical practice.